Prévention et Contrôle de la Fièvre de la Vallée du Rift au Sénégal - Hachim Said, Shakira (International Livestock Research Institute, 2025)
This document presents the AICCRA–Senegal initiative led by the Ministry of Agriculture, Food Sovereignty and Livestock to establish an integrated digital system for monitoring and responding to RVF. Drawing on lessons learned from the 2006–2007 epidemic in Kenya, the project aims to anticipate outbreaks by integrating climate and environmental data (rainfall, heat, pastures), animal and human health data, and field monitoring. The methodology involves defining the data to be collected, developing the platform, providing targeted training and conducting a pilot phase in priority areas. The Ministry plays a central role in coordinating and standardising information flows and operationalising alerts and measures (vaccination, vector control). The ultimate goal is to reduce risks to livestock and public health through faster and better-informed decision-making.